2015
DOI: 10.1186/s12978-015-0109-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of teenage hospital births at the buea health district, South West Region, Cameroon

Abstract: BackgroundTeenage pregnancy is a high-risk condition that requires skilled antenatal care for good outcome. World estimates in 2008 report about 16 million births to adolescent mothers, most of them occurring in low and middle-income countries. In Cameroon, about 12 % of all births are to adolescent mothers. This study determines the prevalence of hospital teenage deliveries in the Buea Health District and compares the delivery outcomes and demographic characteristics between pregnant teenage mothers (14–19) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
63
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 37 publications
18
63
6
1
Order By: Relevance
“…In our univariate analysis adolescence was associated with LBW or PTB, as already demonstrated elsewhere [3,4,18,19,21,30,31]. Conversely studies from Nigeria and Brazil showed no association between maternal age and LBW or preterm birth [32,33].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In our univariate analysis adolescence was associated with LBW or PTB, as already demonstrated elsewhere [3,4,18,19,21,30,31]. Conversely studies from Nigeria and Brazil showed no association between maternal age and LBW or preterm birth [32,33].…”
Section: Discussionsupporting
confidence: 57%
“…In other sub Saharan countries the rates were lower, but not homogenous [2,12,19,21,26]. This maybe reflects behavioral and cultural diversity among pregnant adolescents across countries [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teenage pregnancy is a high risk condition that requires skilled antenatal care for good maternal and fetal outcome (Table 2), adolescent pregnancies occur throughout the world, with estimated 16 million births to adolescent mothers, most of which occur in middle and low income countries [12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk of (Tebeu PM, 2011). However, teenagers still contribute for 9.3 to 14.23% of deliveries in (Egbe TO, 2015 …”
Section: Introductionmentioning
confidence: 99%